Reorientation of Transformational Leadership in Constructing Organizational Culture in Educational Institutions: (Reorientasi Kepemimpinan Transformasional dalam Mengonstruksi Budaya Organisasi di Lembaga Pendidikan) - Evy Hanifah; Yudo Dwiyono; Nur Khayati; Ellen Rotua Basaria Sitorus; Risna Herjayanti; Ranto Setiyono (PT. Berkah Smart Academica, 2025)
This study aims to specifically examine the dynamics, regulations, and milestones in the development of Islamic education in Indonesia within the specific periods of the Old Order, New Order, and the Reform era. This study is a literature review (library research) originating from library materials using a qualitative approach and historical analysis methods. Data exploration was conducted through the identification, in-depth examination, and synthesis of historical documents, books, and reputable scientific journals published in the last five years. The results indicate significant policy shifts across eras: the Old Order laid the legal foundation via Education Act No. 4 of 1950, the New Order focused on curriculum unification via the 1975 Joint Ministerial Decree and system integration through Act No. 2 of 1989, and the Reform era solidified total equality through the National Education System Act No. 20 of 2003. This integration led to the transformation of madrasahs and pesantren, which functioned not only as moral-religious strongholds but were also legally recognized as co-equal educational institutions capable of producing high-quality national human resources.